2015
DOI: 10.1016/j.pbb.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in the aversive memory of mice in the inhibitory avoidance task but not in the elevated plus maze through intra-amygdala injections of histamine

Abstract: Our data indicate that the amygdaloid histaminergic system could modulate anxiety-related behaviors in the EPM and impair the retrieval process in fear conditioning with a strong aversive stimulus. These results contribute further evidence of the distinct histaminergic influence on different emotional pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The EPM test, which was originally developed to estimate anxiety in rodents [28], was modified to evaluate spatial learning and memory in mice. The parameters measured are not the same: the number of entries into the open and closed arms, the time spent in the open arms for anxiety but for memory processes, the transfer latency, which reflects the time the mice took to move from the open arm to either of the enclosed arms [29,30]. In agreement with previous studies, scopolamine injection caused prolongation of transfer latency into enclosed arms suggesting impairment of learning and memory [31,32].…”
supporting
confidence: 74%
“…The EPM test, which was originally developed to estimate anxiety in rodents [28], was modified to evaluate spatial learning and memory in mice. The parameters measured are not the same: the number of entries into the open and closed arms, the time spent in the open arms for anxiety but for memory processes, the transfer latency, which reflects the time the mice took to move from the open arm to either of the enclosed arms [29,30]. In agreement with previous studies, scopolamine injection caused prolongation of transfer latency into enclosed arms suggesting impairment of learning and memory [31,32].…”
supporting
confidence: 74%
“…Previous studies conducted in our group research showed that cerebellar histaminergic system participation in the consolidation of emotional memory is dependent on an anxiety or fear component (GIANLORENÇO et al, 2013); furthermore, the amygdalar histaminergic system induces impairment in the aversive memory in IAT but not in the EPM, suggesting that HA modulates the systems involved in anxiety and fear learning differently (DAHER et al, 2015). Furthermore, the operational need to define anxiety versus fear arises from the conceptions that these two categories of emotion are mediated by shared as well as independent subsystems in the brain (DAVIS et al, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, microinjections of HA in the same dose enhances memory consolidation of inhibitory avoidance learning in mice (GIANLORENÇO et al, 2013), which suggests a different role for the same dose of histamine in a memory model that uses punishment. A study conducted by Daher et al (2015) showed that the amygdaloid histaminergic system could modulate anxiety-related behaviors in the EPM and impair the retrieval process in fear conditioning with a strong aversive stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panksepp (1998a) localized both the fear and rage systems to the neural pathway running from the amygdala, via the medial hypothalamus, down to the mesencephalic periaqueductal gray, although within the amygdala, the two systems can be clearly differentiated, with the fear system being more lateral and the rage system being more medial. Evidence repeatedly shows that the amygdala contributes to the acquisition of Pavlovian fear conditioning and the modulation of memory consolidation of inhibitory avoidance (Daher & Mattioli, 2015;Moscarello & LeDoux, 2013;Wilensky, Schafe, & LeDoux, 2000;Zinn et al, 2009). At the moment of retrieving learned inhibitory avoidance, the entorhinal cortex seems to act as an efferent output of the amygdala and hippocampus (Izquierdo & Medina, 1993).…”
Section: The Constancy Of Dream Contentmentioning
confidence: 99%